NAMES OF PERSONS, THINGS, OBJECTS AND PLACES RELATED TO MOURNING IN UZBEK AND GERMAN LANGUAGES (Scientific journal of the Fergana State University, 2023)
In this following  article  places, person,  things- objeccts,  meaning  subject names which is related to mourning ceremony in German and  Uzbek languages will be analyzed and similarities and differences of them will be revealed with the help of examples in Uzbek and German languages.